THE SUBJECT OF THE EXPERTISE OF LAW IN CRIMINAL PROCESS - D. V. Zotov (Теория и практика судебной экспертизы, 2015)
The subject of legal expertise in the criminal proceedings, under which the author proposes to consider the establishment on the basis of legal knowledge the circumstances for the determination of rights and the circumstances of the act faces legal regulations is explained.